Influence the psychology of persuasion - Cialdini, Robert B. (New York Harper Collins, 2007)
Influence, the classic book on persuasion, explains the psychology of why people say "yes"?and how to apply these understandings. Dr. Robert Cialdini is the seminal expert in the rapidly expanding field of influence and persuasion. His thirty-five years of rigorous, evidence-based research along with a three-year program of study on what moves people to change behavior has resulted in this highly acclaimed book.
Includes index
Keywords: Influence (Psychology)